Improve Cognitive Development Through Rainbow Milk Games - Wulandari Retnaningrum; Tri Wahyuni (Early Childhood Education Development and Studies (ECEDS), 2022)
This study aims to determine the process and results in learning activities as an effort to improve the cognitive development of B2 group children at RA Ma’arif NU 04 Istiqomah Kalisabuk, Cilacap Regency through the rainbow milk game. This type of research is Classroom Action Research (CAR) using Kurt Lewin’s design. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The research subjects were the children of group B2 RA Ma’arif NU 04 Istiqomah Kalisabuk. Data collection techniques were carried out through observation, interviews and documentation. The collected data were analyzed using qualitative and quantitative descriptive approaches. The validation test technique uses construct validity. The results showed that the cognitive development of children before the action was still in the undeveloped category, namely 45,21%. The results of the first cycle showed cognitive development increased to 68,37% in the developing category. In the second cycle, it became 86,23% in the very well develop category. Rainbow milk game has a very good impact. This is indicated by an increase in cognitive development compared to before the action.